(untitled) (Medico Legal Update, 2019)
Background/Objectives: The purpose of this study is to identify changes in the muscle activity of the trunk and lower extremity during squats with various interventions(general squats, machine squats, laser squats). Method/Statistical Analysis: 18 people were selected to measure the muscle activity of the elector spinae(ES), gluteus maximus(GM), vastus medialis oblique(VMO), and vastus lateralis(VL). One-way Anova with repeated measurements was conducted to determine the difference in muscle activity in various squats intervention. The Bonferroni correction was used as a post-test to check the difference in muscle activity between the various interventions, and the significance level was set to 0.05. Statistical programs used SPSS Version22.0(Statistics Package for the Social Science). Findings: There were significant differences in GM, VMO and VL during the various squat interventions. GM showed higher muscle activity in machine squats than general squats. VMO showed higher muscle activity machine squats than general squats and laser squats during descending phase. VL showed higher muscle activity in machine squats than general squats and laser squats during descending and holding phase. Improvements/Applications: This study suggests that machine squat is effective as an intervention to increase muscle activity of GM and VMO during squat exercise.